The Role of Organizational Culture and Job Satisfaction in Enhancing Employee Performance in the Hospital Sector - Paskalia Aek Klau; Maria Widyarini; Kevin Grahadian (Research Synergy Foundation, 2025)
This study examines the influence of organizational culture and job satisfaction on employee performance at Private Hospital Type C, Central Java. Hospitals face unique human resource management challenges, including high workloads and expectations for service quality, making organizational culture and job satisfaction critical to optimizing performance. Using a quantitative approach, data were collected from 201 healthcare workers through a structured questionnaire utilizing a Likert scale. The data were analyzed using descriptive statistics and linear regression. The findings reveal that both organizational culture and job satisfaction significantly affect employee performance, with strong statistical significance. The variance in employee performance is explained by these two factors by 65.1%. These results confirm that a positive organizational culture and high job satisfaction contribute substantially to enhancing staff performance in hospital settings. The findings also align with the hospital’s mission, vision, and core values, emphasizing holistic care, teamwork, and professional integrity. Strengthening organizational culture and addressing job satisfaction can serve as effective strategies for hospital management to improve service quality and operational efficiency